ANALISIS LAJU DEGRADASI PADA PERMUKAAN BAHAN ISOLASI RESIN EPOKSI SILANE KONDISI PENUAAN DIPERCEPAT - , Yanolanda Suzantry Handayani, Prof. Dr. Ir. T. Haryono, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Polymer is now developed as the material replacement of porcelain isolator and glass insulators. However, tropical climates and high rainfall can cause problems to them. Ultraviolet radiation will continuously accelerate to the surface of the polymer insulator material surface. As a result, the surface of the insulating material let a current flowing easier and making the degradation rate of the surface of the insulator material faster. Materials used in this study were made from epoxy resin diglycidyl ether of bisphenol-A (DGEBA) as the base material, and metaphenylen diamine (MPDA) as the reinforcement material and silica sand. DGEBA and MPDA composition was 30% silica sand filler 30%, 25%, 20%, 15%, 10% and 10% silicone rubber was 15%, 20%, 25%, 30%. The size of the test material was 120 mm x 50 mm x 5 mm. The study was conducted in the laboratory according to standard IEC 587 :1984. This study was conducted to determine the effect of ultraviolet radiation on hydrophobic contact angle and surface damage on the broad value of insulation material epoxy resin silanes. The results showed that the length of time of exposure to UV light tends to make a material value of the contact angle and the greater the leakage current on the surface of the material will be increased so as to accelerate the rate of surface degradation.